A case study in distributed team science in research using electronic health records. (2018) - Song, Jiao; Elliot, Elizabeth; Morris, Andrew D; Kerssens, Joannes J; Akbari, Ashley; Ellwood-Thompson, Simon; Lyons, Ronan A
No abstract available